(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the demographic analysis of diagnosed cases of syncope patients on head up tilt test Study Design: cross sectional analytical study Place and Duration of Study: This study was conducted at the Islamic International Medical College and in Armed forces Institute of Cardiology, Department of Electrophysiology, Rawalpindi from April 2017 to March 2018. Materials and Methods: In this study 70 cases were taken on the basis of their past record of syncope, episodes of syncope and on the basis of their findings of head up tilt test. During the collection of the data of syncope, their age, gender, episodes of syncope, occupation and pattern of syncope was observed. The descriptive analysis of collected data was represented as mean ± standard deviation on SPSS statistics version 21. Results: In Analysis of Demographic data we took 70 cases of syncope among these there were 15 females and 55 males. Mean age of the syncope patients were 36.17± 11.93, while the episodes of syncope were mean of 2.90 ± 1.83. In our Analysis of syncope, we also found that among 70 cases, 41 of the positive cases were soldiers or belongs to army because of prolong standing during duty hours. During this study two patterns of syncope were observed which were vasovagal syncope and Postural tachycardia syndrome. Conclusion: we conclude that syncope is more prevalent in middle age groups and most of the patients presents with 2 or more episodes of syncope. Syncope is more prevalent in those who are more prone to prolong standing at work.